Resilience and vulnerability in very preterm 4-year-olds. Issue 5 (4th July 2021) - de Silva, Aryanne; Neel, Mary Lauren; Maitre, Nathalie; Busch, Tyler; Taylor, H. Gerry
Abstract: Objective: The primary goal was to determine the prevalence and correlates of adaptive competence in 51 very preterm (VPT, gestational age ≤30 weeks) 4-year-old children compared to a group of 35 term-born (Term) children of the same age. Methods: Adaptive competence, or "resilience" in the VPT group, was defined as age-appropriate scores on tests of early literacy and numeracy and an absence of clinical elevations on parent ratings of problems in behavior and development. Analyses were conducted to compare groups in the prevalence of adaptive competence, determine how adaptively competent VPT children differed from children who were not adaptively competent (i.e. the "maladaptive" subset) and from adaptively competent Term children, and identify family factors related to competence independent of group. Results : Controlling for sociodemographic background, fewer VPT children compared to Term participants (31% vs. 71%) were adaptively competent ( p = .026). Compared to the maladaptive subset of the VPT group, adaptive VPT children had higher scores on cognitive tests and more positive parent ratings of executive function and self-regulation. The adaptive VPT subset had outcomes similar to adaptive Term children on many measures but poorer outcomes in specific domains. Higher home stimulation for learning and lower parent distress were also related to adaptive competence. Conclusion: Although a substantial minority of VPT children display adaptive competence, these children may have weaknesses in cognitive skills and executive functioning that present developmental challenges. Associations of adaptive competence with supportive home environments suggest that early family intervention may improve outcomes in this population.